Changes in antioxidants are critical in determining cell responses to short‐ and long‐term heat stress. Issue 1 (31st May 2014) - Sgobba, Alessandra; Paradiso, Annalisa; Dipierro, Silvio; De Gara, Laura; de Pinto, Maria Concetta
<x xml:space="preserve">Abstract</x> Heat stress can have deleterious effects on plant growth by impairing several physiological processes. Plants have several defense mechanisms that enable them to cope with high temperatures. The synthesis and accumulation of heat shock proteins (HSPs), as well as the maintenance of an opportune redox balance play key roles in conferring thermotolerance to plants. In this study changes in redox parameters, the activity and/or expression of reactive oxygen species (ROS) scavenging enzymes and the expression of two HSPs were studied in tobacco Bright Yellow‐2 (TBY‐2) cells subjected to moderate short‐term heat stress (SHS) and long‐term heat stress (LHS). The results indicate that TBY‐2 cells subjected to SHS suddenly and transiently enhance antioxidant systems, thus maintaining redox homeostasis and avoiding oxidative damage. The simultaneous increase in HSPs overcomes the SHS and maintains the metabolic functionality of cells. In contrast the exposure of cells to LHS significantly reduces cell growth and increases cell death. In the first phase of LHS, cells enhance antioxidant systems to prevent the formation of an oxidizing environment. Under prolonged heat stress, the antioxidant systems, and particularly the enzymatic ones, are inactivated. As a consequence, an increase in H2O2, lipid peroxidation and protein oxidation occurs. This establishment of oxidative stress could be responsible for the increased cell death. The rescue of cell growth and cell viability, observed when TBY‐2 cells were pretreated with galactone‐γ‐lactone, the last precursor of ascorbate, and glutathione before exposure to LHS, highlights the crucial role of antioxidants in the acquisition of basal thermotolerance.